I have the following proof of the sun rule for sequences : We have the two sequences $(a_n)$ and $(b_n)$ where $(a_n)\rightarrow a $ and $(b_n)\rightarrow b $. We also observe that $$0\leq |c(a_n-a)+d(b_n-b)|\leq |c||a_n-a|+|d||b_n-b| .$$ We know that both $(a_n-a) $ and $(b_n-b)$ are null sequences so using sum rule and sandwich theorem for null sequences (take as given here) we conclude that $(c(a_n-a)+d(b_n-b))\rightarrow 0 $ so $$(ca_n+db_n-(ac+bd))\rightarrow 0 \ \Rightarrow (ca_n+db_n) \rightarrow ac+bd , $$ since $(x_n-x)\rightarrow 0 \iff (x_n)\rightarrow x. \ \ \square $

Is this a valid proof or are there holes?


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Browse other questions tagged or ask your own question.